METAPHOR ANALYSIS IN THE HIKAYAT SI MISKIN AS CLASSICAL MALAY LITERATURE - Subagiharti, Heni; Handayani, Diah Syafitri (English Review: Journal of English Education, 2025)
Hikayat Si Miskin is one of the classical Malay literary works that is rich in cultural and moral values. In this work, the use of metaphors is one of the main tools to convey symbolic messages and enrich the aesthetics of the story. This study aims to analyze the metaphors contained in Hikayat Si Miskin using a semiotic approach and classical literary studies. This study found that the metaphors in this text function to describe the social struggle, religiosity, and dynamics of the main character's life. For example, "poverty" in the story not only describes the material condition, but also becomes a spiritual symbol for the journey towards awareness and devotion to God. In addition, natural metaphors, such as "sea" and "mountain," are used to represent the challenges of life that must be faced by the main character. This analysis shows that Hikayat Si Miskin not only stores narrative richness, but also offers insight into how classical Malay society understands life and universal values. The results of this study are expected to contribute to the study of classical Malay literature and broaden appreciation of the use of metaphors in the Nusantara literary tradition.